Reduced gene expression levels after chronic exposure to high concentrations of air pollutants - Rossner, Pavel; Tulupova, Elena; Rossnerova, Andrea; Libalova, Helena; Honkova, Katerina; Gmuender, Hans; Pastorkova, Anna; Svecova, Vlasta; Topinka, Jan; Sram, Radim J (Mutation research, 2015)
We analyzed the ability of particulate matter (PM) and chemicals adsorbed onto it to induce diverse gene expression profiles in subjects living in two regions of the Czech Republic differing in levels and sources of the air pollution. A total of 312 samples from polluted Ostrava region and 154 control samples from Prague were collected in winter 2009, summer 2009 and winter 2010. The highest concentrations of air pollutants were detected in winter 2010 when the subjects were exposed to: PM of aerodynamic diameter <2.5μm (PM2.5) (70 vs. 44.9μg/m(3)); benzo[a]pyrene (9.02 vs. 2.56ng/m(3)) and benzene (10.2 vs. 5.5μg/m(3)) in Ostrava and Prague, respectively. Global gene expression analysis of total RNA extracted from leukocytes was performed using Illumina Expression BeadChips microarrays. The expression of selected genes was verified by quantitative real-time PCR (qRT-PCR). Gene expression profiles differed by locations and seasons. Despite lower concentrations of air pollutants a higher number of differentially expressed genes and affected KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways was found in subjects from Prague. In both locations immune response pathways were affected, in Prague also neurodegenerative diseases-related pathways. Over-representation of the latter pathways was associated with the exposure to PM2.5. The qRT-PCR analysis showed a significant decrease in expression of APEX, ATM, FAS, GSTM1, IL1B and RAD21 in subjects from Ostrava, in a comparison of winter 2010 and summer 2009. In Prague, an increase in gene expression was observed for GADD45A and PTGS2. In conclusion, high concentrations of pollutants in Ostrava were not associated with higher number of differentially expressed genes, affected KEGG pathways and expression levels of selected genes. This observation suggests that chronic exposure to air pollution may result in reduced gene expression response with possible negative health consequences.
Keywords: Gene Expression Regulation; Human health; Male; Air pollution; Česká republika; Adult; dospělí; mužské pohlaví; Polycyclic aromatic hydrocarbons; stanovení celkové genové exprese; Oligonucleotide Array Sequence Analysis; látky znečišťující vzduch; Gene Expression Profiling; Chronic exposure; Czech Republic; leukocyty; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; lidé; roční období; Seasons; Humans; regulace genové exprese; Leukocytes; Environmental Exposure; Gene expression profiles; Particulate matter; lidé středního věku; vystavení vlivu životního prostředí; Middle Aged; Air Pollutants